Korelasi antara Keterampilan Komunikasi dengan Hasil Belajar Kognitif Peserta Didik Kelas X - Karin Fitri Mekar Sari; Mimien Henie Irawati; Hari Santoso (LPPM Institut Pendidikan Nusantara Global, 2025)
Communication skills are one of the essential 21st-century competencies for students because they play an important role in conveying ideas, understanding learning materials, and building cooperation and exchanging ideas during the learning process. This ability is closely related to the achievement of optimal cognitive learning outcomes. This study is a quantitative study using a survey method conducted in September–October 2025 at SMAN 2 Batu. The study population was grade X students, with a sample of 107 students selected using purposive sampling. The communication skills instrument used a questionnaire containing 10 statements adapted from Greenstein (2012), while cognitive learning outcomes were measured using a multiple-choice test consisting of 10 questions based on Anderson and Krathwohl's (2001) revised Bloom's taxonomy, covering six dimensions: remembering, understanding, applying, analyzing, evaluating, and creating. Data analysis was performed using Pearson's correlation test and simple linear regression using SPSS 23. The results showed that students' communication skills were in the high category with an average score of 36.94, while cognitive learning outcomes were in the moderate category with an average of 6.29. The Pearson correlation test produced a value of r = 0.883 with a significance of < 0.001, indicating a positive and very strong relationship. A positive correlation coefficient value indicates that the higher the communication skills of students, the higher their cognitive learning outcomes. Thus, communication skills are an important ability that contributes to improving the cognitive learning outcomes of students.